Linking administrative data on children's social care to investigate the outcomes of provision - Rick Hood; Allie Goldacre (International Journal of Population Data Science, 2023)
Objectives This paper will present findings from a study of linked administrative data on children’s social care (CSC) services in England. Its objectives were to identify and profile the underlying categories of demand for CSC services in England and compare the outcomes of provision between these categories, using a range of measures.